PENGARUH PERACUNAN TRIKLOPIR DAN POLA PENGGERGAJIAN TERHADAP SIFAT PENGGERGAJIAN KAYU RASAMALA (ALTINGIA EXCELSA NORONHA) - Osly Rachman; Jamal Balfas (Jurnal Penelitian Hasil Hutan, 1989)
The  objective  of  this study   is to determine   the  sawing properties   of  triclopyr  poisoned   rasamala logs compared   to the girdled and normal ones.   The effect  of sawing pattern  on sawing properties   were also observed.The  log samples  used  in this  experiment  comprise  of  18 pieces  which  were collected  from  three different groups  of tree  (poisoned   and  girdled  in one  year periode,   and control).   Six  logs of  each group  were sawn  in two  sawing patterns, namely   live sawing  and  semi-quarter   sawing.   Parameters  of  sawing observed  include  recovery,  productivity,  power   con- sumption,   and sawn timber  defects,  particulary  splits and bowing.The  results  of  study   revealed  that  moisture  content   of poisoned   logs was 20%  lower  than  the  normal  one.   Mean-while,   both  moisture  content  of girdled logs and poisoned   ones are not significantly  diferent.       Poisoning  treatment   on  rasamala trees  in comparison   to girdled and normal ones did not show  significant  difference in  any  sawing properties,   except   sawing productivity.   The  sawing  recovery,  power   consumption,    splits  and  bowing  of sawn  timber  were  62%;  32.37  watt  sec./cm2,     5.21   cm  and  3.91   cm,   respectively.   The  live sawing could  increase the pro- ductivity as much  as 0.18   m3 /hour  higher than semi-quarter   sawing.